Booksnaps or Ms Word? Which One Is Better in Developing Reading Comprehension across Critical-Creative Thinking Levels - Yohana, Elva; Cahyono, Bambang Yudi; Suryati, Nunung; Astuti, Utari Praba (JEELS (Journal of English Education and Linguistics Studies), 2024)
The study investigates which of the two summary writing techniques (one using BookSnaps and the other using MS-Word) affects reading comprehension performance better than the other.  It also examines whether or not level of critical-creative thinking skills affects the results. This study used a causal-comparative design. Two groups of students were involved in this study and after the treatment they were tested on their reading comprehension performance across critical-creative thinking skill levels. The results showed that the reading comprehension performance of the two groups of students were not different significantly regardless of the summary writing techniques used. The results also showed that students with high level of critical-creative thinking skill outperformed the students with low critical-creative thinking skill in each of the two groups. This implies that teachers might use either BookSnaps or MS- Word to train the students in summary writing. However, when dealing with students with low critical-creative thinking level, the teachers might give more time in the process of summary writing or give assistance to students who need it when applying either BookSnaps of MS-Word.